DEVELOPING STUDENTS’ THINKING PROCESSES THROUGH PSYCHODIAGNOSTICS AND PSYCHOCORRECTION IN SCHOOL PRACTICE - Samarova Shohista Rabidjanovna (Modern American Journals, 2026)
This article discusses a practice-oriented framework for psychodiagnostics and psychocorrection of students’ thinking processes in general secondary education. The paper conceptualizes thinking as a multi-component system (analytical reasoning, cognitive flexibility, executive regulation, and metacognitive control) that develops unevenly under the influence of learning conditions, emotional state, and communicative environment. The central problem addressed is the mismatch between curricular demands for higher-order thinking and the limited use of systematic school-based psychological assessment and correction programs. The article proposes a staged model that includes (1) screening and hypothesis-building, (2) targeted assessment of key thinking-related functions (attention control, working memory, cognitive flexibility, reasoning), (3) individual and group feedback, and (4) psychocorrection through structured cognitive training, metacognitive strategies, and classroom-integrated supports. To avoid “labeling” students, the framework emphasizes dynamic assessment principles, developmentally focused interpretation, and collaboration among psychologist, teacher, and parents. The expected outcomes of the proposed approach include clearer identification of learning-related cognitive barriers, improved self-regulation and task planning, reduction of avoidant academic behavior, and the formation of sustainable learning strategies. The article also highlights ethical and methodological requirements, including confidentiality, cultural and linguistic sensitivity, careful interpretation, and the prevention of diagnostic bias. The presented framework can be adapted to school resources and may serve as a methodological basis for developing local psychodiagnostic protocols and intervention modules.
Keywords: Thinking processes; psychodiagnostics; psychocorrection; executive functions; metacognition; school psychology; cognitive development.